Impact of electrolytic hydrogen charging on the mechanical properties and microstructure of AISI 304 austenitic stainless steel - Abboub, Amar; ABOURA, Ahmed; BENMAHDI, Khaled; SADOUN, Mohamed; boukhelef, Mohamed (Vojnotehnički glasnik / Military Technical Courier, 2025)
Introduction/purpose: Hydrogen embrittlement (HE) substantially decreases the mechanical properties of austenitic stainless steels, constraining their efficacy in diverse applications. This study examines the impact of electrolytic hydrogen charging on the mechanical characteristics and microstructure of AISI 304 stainless steel, a commonly utilized grade. Methods: Tensile specimens measuring 8 mm in diameter were produced through machining and subjected to hydrogen loading electrolytically at different times in a glass chamber containing sulfuric acid (H2SO4) at 0.05M. Mechanical tests were conducted using a Karl Frank GMBH tensile testing universal machine type: 83431. The samples underwent microscopic analysis using optical microscopy (OM), x-ray diffraction (DRX), and scanning electron microscopy (SEM). The experimental characterization involved producing cylindrical specimens, which underwent heat treatments (austenization) ranging from quenching to tempering, followed by immersion in a cold heat treatment cycle at -196°C for 35 minutes. Hydrogen pre-loading was carried out electrochemically-hydrogen charged for different loading times in hours.Results: Results showed that the effects of hydrogen embrittlement (HE) on AISI304 stainless steel are characterized by a decrease in ductility, sometimes undergoing sudden embrittlement. This phenomenon is consistent with other authors who have demonstrated a loss of ductility due to the martensitic transformation of austenite caused by deformation and hydrogen diffusion.Conclusion: Inclusions, such as second-phase particles, carbide precipitates, inclusions of small, medium, or large size, interfaces, and interphases, can be considered inclusions. Their mechanical properties and hydrogen transport and segregation mechanisms differ from those of the matrix, particularly in martensitic structures. The observation of optical dark area (ODA) and black spots indicates that hydrogen is concentrated either in the molecular form H2 or combined with Sulphur in the form H2S.
Keywords: AISI304 Stainless steel, Heat treatment, Mechanical properties, Hydrogen charged, Hydrogen embrittlement, Microstructure.